Bagaimana Pendidikan Ekonomi Keluarga Membina Perilaku Ekonomi Siswa dalam Wirausaha - Shobachatunnajah, Nora Rosyidah Nur; Kurniawan, Riza Yonisa (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2025)
Understanding economic behavior will be useful for students in menanging their economy and finances when living apart from their parents. This research aims to study the impact of family economic behavior and examine the role of economics and entrepeneurship. Research data wa collected through an online survey from 88 students, and structural equation modelling whit IBM-SPSS 24 statistics wa used to confirm the proposed hypothesis the research results show that there is a close relationship between family economic behavior. Likewise, family economic education can improve students’ economics and entrepreneurship. This research also confirms the direct influence between economics, entrepreneurship and students’ economic behavior. Finally, this research notes the important role of economics and entrepreneurship in mediating the relationship between family economic education and students’ economic behavior. The results of this research provide valuable insights for policy research provide valuable insights for this research provide valuable insights for policy research and educational institutions on how to engage economics and entrepreneurship to question economic behavior among students.